Comprendre le changement institutionnel - Arnaud Buchs (Revue de la Régulation)
This paper presents the analytical contribution of the “water use mode”. In the context of a new syncretic institutionalist approach that aims at exploring the “institutional Bermuda triangle” – i.e. the articulation of beliefs, institutions and behaviours –, the water use mode helps to understand the evolution of water use. It shapes our empirical corpus based on a historiographical analysis of the evolution of water use in the agricultural sector in Almeria between the late nineteenth century and today. On the one hand, the water use mode allows us to describe the evolution of uses in four periods: the first three correspond to the phases of genesis, regime and crisis of a particular water use mode, while the fourth one reflects the emergence of a new mode to address the limitations of the previous one. On the other hand, we mobilize the theoretical approach to characterize the first mode stamped as “hydraulicist” and to understand the determinants of its crisis. Finally, we show how the new mode attempts to address the limitations of the previous mode. Nevertheless, it actually does not imply a paradigm shift but corresponds to a “crisis regime”.